Analysis of the Effectiveness of Using Digital Technologies in Teaching 1st Year Medical Students - Popovich, Alisa; Aliyeva, Olena (Освітні виклики, 2024)
In the modern world, the amount of knowledge has increased significantly, and therefore, there is a constant need to acquire and update it. Medicine is a rapidly developing field, and it is important for the future and working doctor to constantly improve their professional skills using modern technologies. The purpose of this study is to determine the most effective modern information technologies and the level of their effectiveness in the study of the subject "Medical Biology," as well as the attitude of students to their use and the impact on the ability to perceive educational material. Methodology. The study employed a complex set of research methods, including theoretical (such as analysis of scientific sources, pedagogical and teaching materials, and comparison) and empirical (such as summarizing teaching experience and interviewing) methods. First-year students (130) of the medical university were involved in the survey. Results. From our experience, using problem lecture technology in the learning process is more appropriate. It is based on a problematic presentation of the material in the form of contradictions, certain contradictions, the discussion of which makes it possible to keep students active, encourage them to dialogue or even debate. Problem presentation of the material stimulates the mental abilities of students and develops critical thinking, scientific, and cognitive activity. For data visualization, in addition to presentations and videos, mind maps were created, which made it possible to direct students not to memorization, but to reflection and awareness of cause-and-effect relationships and connections. The most effective way to create a mental map is to use the "brainstorming" technology. Students offer several variants of ideas for solving a specific problem; everyone expresses their own opinion and then combines the information into one collective solution and depicts it in the form of a diagram. To combine theoretical training and practical skills (simulating biological processes), we used the Labster platform covering different topics in biology, such as genetics, ecology, and cell biology. When studying Medical Biology, the most popular platform used by students was edX (53.1%). Regarding the forms of education, 37.9% of respondents chose the form, 38.6% the mixed form, and the rest were undecided. Conclusions. Modern information technology has become an integral part of the learning process in medical higher education, improving the quality of students’ preparation for the requirements of modern medicine. The most effective methods for teaching "Medical Biology" include problem-based lectures with presentations, electronic resources, videos, virtual labs, websites, and mind maps. A blended approach that combines multiple technologies enhances the learning process and helps develop essential professional skills in future doctors.